PLC Based Automatic Stamping Machine for labelling the Boxes - Pie, Khin Thet; Hlaing, May Su; Hla, Tin Tin (AI Society & STMIK Indonesia, 2025)
Stamping machine plays a vital role for automation industy. There have consisted of two main parts. The results of this system has been demonstrated with supervisory control and data acquisition (SCADA) systems software and hardware. MS 32MT PLC has been applied to control and sensors and limit switches has been used to get good accuracy and start and stop condition of this system. The combination of PID and PLC have been and the desired value in conveyor system aims to maintain and the the system is stable. This system has been used for labelling the boxes in automation industry that have been carried on conveyor and chosen the box’s size by the use of laser distance sensors at robot arm system. The correct box’s size has been detected with proximity sensor and stamped the boxes. The aim of automatic stamping machine is the prototye machine to apply in automation industry.